Аналіз технологій отримання олії з олійних культур - Дідур, В. В.; Журавель, Дмитро Павлович; Шокарев, Олександр Миколайович; В’юник, Ольга Володимирівна; Комар, Артем Станіславович; Didur, V.; Zhuravel, Dmytro; Shokarev, Oleksandr; Viunyk, Olha; Komar, Artem (Запоріжжя : 2022, 2022)
UA: Рослинна олія – продукт, який у наш час має великий попит. В статті надано результати аналізу наукових робіт, присвячених дослідженню технологій отримання олії з різних олійних культур. Рослинна олія є певним видом харчових жирів. Сировиною для виробництва рослинних олій є плоди і насіння олійних рослин, в яких олії накопичуються у великих кількостях, при цьому можлива їх виробнича переробка для вилучення олій. Залежно від очищення рослинні олії діляться на такі види – рафінована, гідратована і нерафінована. Спосіб виробництва та ступінь очищення олії впливають на фізико-хімічні та органолептичні показники рослинної олії. Існують такі способи отримання рослинної олії з насіння: механічний, хімічний, комбінований. В роботі описано існуючі технології переробки насіння різних олійних культур. Встановлено, що метод пресування є якісним способом виробництва рослинної олії. Наведено схему класифікації шнекових пресів. EN: Vegetable oil is a product that is in great demand nowadays. The article presents the results of the analysis of scientific works devoted to the research of technologies for obtaining oil from various oil crops. Vegetable oil is a type of dietary fat. The raw materials for the production of vegetable oils are the fruits and seeds of oil plants, in which oils accumulate in large quantities, while their production processing is possible for the extraction of oils. Depending on the purification, vegetable oils are divided into the following types: refined, hydrated and unrefined. The production method and degree of oil purification affect the physicochemical and organoleptic parameters of the vegetable oil. There are the following methods of obtaining vegetable oil from seeds: mechanical, chemical, combined. The work describes existing technologies for processing seeds of various oil crops. It has been established that the pressing method is a high-quality method of vegetable oil production. Used screw oil presses have similar working bodies, general scheme of operation and devices. The main working elements of the screw oil press are the screw cylinder and the screw shaft. The final products of the process are pressed vegetable oil and cake. The use of screw presses allows you to ensure the continuity of technological operations, increase the yield of oil from seeds, automate the technological process, facilitate the work of service personnel, improve the sanitary conditions of workshops, and exclude the use of press cloth. Screw presses are currently the most effective equipment for removing oil from oil crops by the press method. The article provides a classification scheme for screw presses.
Analysis of oil production technologies from oil crops
Дідур В. В., Журавель Д. П., Шокарев О. М., В’юник О. В., Комар А. С. Аналіз технологій отримання олії з олійних культур. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 180-189.
Keywords: аналіз; технологія; рослинна олія; пресування; analysis; technology; vegetable oil; pressing